ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KARET ALAM INDONESIA KE SINGAPURA TAHUN 1980-2010 - Onike Siburian (Economics Development Analysis Journal, 2012)
Indonesia is one of the major producen of natural rubber in the world. Singapore is one of Indonesia’s largest exports of natural rubber in Southeast Asia. Malaysia and Thailand are also a major producer of natural rubber in the world but they did not export to Singapore. In 1990 and 2010 Indonesia’s natural rubber exports to Singapore have decreased. This research aims to analyze the factors that affect the export of natural rubber Indonesia to Singapore. The methods that used in this research are error correction model (ECM). Singapore’s GDP in the short run have a positive relationship to the natural rubber exports of Indonesia to Singapore and in the long run GDP has a negative relationship. Indonesia’s natural rubber prices have a negative relationship to exports of natural rubber Indonesia to Singapore in both the short and long run. Indonesia’s natural rubber production has a positive relationship in export of natural rubber Indonesia to Singapore in both the short and long run. Indonesia should increase the production of natural rubber to increase exports of natural rubber and will increase the national income of Indonesia.